Vegetable leather pada berbagai perbandingan rumput laut (Eucheuma cottonii) dan daun beluntas (Pluchea indica L.) : evaluasi sifat sensori dan fisik - Chintia Agrefina Brilian; Sussi Astuti; Sri Hidayati; Fibra Nurainy (Jurnal Teknologi & Industri Hasil Pertanian, 2023)
Vegetable leather can be produced from beluntas leaves which have a high crude fiber content mixed with hydrocolloid compounds such as seaweed (Eucheuma cottonii) as a binder. The purpose of the study was to obtaini a comparison ofi beluntas leavesi and seaweed E. cottonii which produced ithe bestasensory and physical properties of vegetable leather. The studye was arranged in a Completely Randomized Block Design (CRBD) withi 6 levels of treatmenti with a comparison ofi beluntas leavesi and seaweed  (Eucheuma cottonii) i.e. 30%:70%; 40%:60%; 50%:50%; 60%:40%; 70%:30% and 80%:20% and 4 repetitions. The data homogeneity and additivity were tested using Bartletti and Tukey tests, then analyzed for varianceeand further itested with LeastaSignificant Difference (LSD) at 5% level. The resultsdshowed the comparison of 30% beluntas leaves : 70% seaweed was found to be the best treatment, which resulted in a texture score of 4.55 (compact), aroma score of 4.30 (not scented with beluntas leaves), taste score of 4.83 (like), color score 4.55 (blackish green) and overall acceptance score 4.42 (like), physical test tensileestrength of 9.43 MPa, percent elongationpof 1.34% and thickness of 0.13 mm. The moisture content of the best vegetable leather was 13.34%, ash content was 19.74%, fat content was 1.29%, protein content was 13.14%, and antioxidant activity was 1576.14 ppm.